Openness to Experience and Activity Engagement Facilitate the Maintenance of Verbal Ability in Older Adults. - Hogan, Michael J.; Staff, Roger T.; Bunting, Brendan P.; Deary, Ian J.; Whalley, Lawrence J. (Psychology & Aging, 2012)
The current study used data from the Aberdeen Birth Cohort, 1936, to investigate the hypothesis that the positive effects of the personality trait Openness on cognitive ability are mediated by activity levels. Results of latent growth modeling analysis revealed that higher Openness predicted better reading ability, inductive reasoning, and memory performance across three testing occasions when participants were aged 64-68 years. Higher Openness predicted higher activity levels, and higher activity levels in turn predicted higher reading ability, but not higher performance on measures of inductive reasoning, memory, and speed of processing. Overall, Openness and activity engagement appear related to preserved higher cognitive ability in older adults, with Openness having a direct effect on marker tests of fluid ability and with the combined influence of Openness and activity being particularly important for marker tests of crystallized intelligence.